Integrated value co-creation and affective commitment in banking industry - Nuri Wulandari; Reza Ashari Nasution (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
Co-creation is a seminal concept in marketing, explained as the engagement between service provider and customer in creating value. This concept has grown into a rich and wide array of studies that have become an area of intense focus in the discipline. Nevertheless, the understanding of the concept, especially in service marketing, is mostly still developing in silos rather than encompassing the entire sphere of value creation. There is a research gap in terms of a measurement scale that is not only integrative, but also encompasses different interaction experiences in the co-creation process. The present research aims to develop a scale measuring integrated value co-creation (IVC) to assess value co-creation in the three spheres of value creation (production, joint and customers' sphere) and try to investigate the impact of IVC on affective commitment (AC). A quantitative survey was administered and a total of 308 respondents in the banking industry have responded. The result confirms the IVC measurement tools with reliability and validity of the construct. It also found a significant and positive relationship between IVC and AC. The study is crucial due to its context in the industry of banking where knowledge on how to innovate becoming the key barrier. The novelty of the study lies in providing empirical evidence of co-creation drive customer commitment. This is achieved through the development of an integrated value co-creation scale that encompasses all spheres of value creation, including customers' direct-indirect interaction and active-passive involvement, in one single construct. The study serves as an important tool during the development stages of co-creation efforts.
Keywords: M31; M10; G20; 650; co-creation; marketing; service dominant logic; value creation sphere; banking; affective commitment